Dependence of red clover production processes on technological elements - H. Ya. PANAKHYD; N. І. KOZAK; В. М. SENDETSKYІ (Передгірне та гірське землеробство і тваринництво, 2022)
One of the most promising agricultural crops is red clover, which can be used as forage for farm animals and for energy purposes. In addition, this crop plays an important agri-environmental role as it helps to improve soil fertility. The aim of this work is to establish the dependence of the production processes of red clover, as the main component of legume-grass agrophytocoenosis, on the use of lime, inoculant, growth enhancers, and phosphorus-potassium fertilizer. The study was conducted in the conditions of a stationary field experiment in the Western Forest-Steppe of Ukraine. Determination of the main parameters of red clover crop formation was carried out by theoretical calculations, which are based on the share of red clover in legume-grass, which originated in 2011.